Kandungan beta karoten, polifenol total dan aktifitas â€merantasâ€ radikal bebas kefir susu kacang hijau (Vigna radiata) oleh pengaruh jumlah starter (Lactobacillus bulgaricus dan Candida kefir) dan konsentrasi glukosa - Supriyono, Teguh; Murwani, Retno; Nurrahman, Nurrahman (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Kefir is a well known fermented dairy milk product which is functional for gut health. However kefir can also be made from vegetable milk such as soy or mungbean milk. Objective: To study the chemicalÂ and functional property of Mungbean milk (MBM) Kefir Methods:Mungbean milk was fermented into MBM Kefir using Lactobacillus bulgaricus and Candida kefir. Three levels of cultures and glucose concentration were tested and a complete randomized design experiment was employed. The resulting MBM Kefir were tested for Î²-carotene level, total polyphenol content, and free radical scavenging activity. Beta carotene level, total polyphenols and free radicals scavenging activity were determined by spectrophotometry, Folin-Ciocalteu method, and DPPH radical scavenging assay respectively. The data were analyzed by ANOVA and when the result of ANOVA was significant, Tukeyâ€™s multiple comparison was conducted. Results: Culture concentration increasedÂ Î²-carotene level (p = 0.049), total polyphenol (p = 0.015) and free radical scavenging activity (p = 0,000) of MBM kefir. Glucose concentration increased total polyphenol (p = 0.002), but had no effect on free radical scavenging activity and Î²-carotene level. However, there were no interaction among treatments at 0.05 significance level. Total acid level ranged from 1.57 to 2.54%, with the highest and level at 15% cultures concentration and 15% glucose concentration. Alcohol level ranged from 0.26 to 0.90% which was in accordance with the maximum standard for kefir (1%). Conclusion: An optimal product of mungbean milk kefir with highest free radical scavenging activity can be obtained using 15% cultures (Lactobacillus bulgaricus and Candida kefir) and 10% glucose concentration.